(untitled) (World of finance, 2023)
Introduction. Digitization of agricultural activities formed the prerequisites for the practical implementation of the philosophy of "precision agriculture" based on geo-information technologies in the functioning of agricultural enterprises. The use of modern geo-information technologies and the global positioning system optimizes not only the processes of cultivating land and growing agricultural products, but also fundamentally changes the methodology and organization of accounting. In particular, accounting of costs for the agricultural machinery operation based on information generated by GPS technology is subject to automation. The purpose of the article is to improve the accounting of operational costs in agricultural activities using the global positioning system and to automate the cost calculation of services provided by agricultural machinery to third-party customers. Results. The expediency of using information generated by GPS navigators about the location of motor vehicles and special equipment, travel routes, mileage, speed of movement, stops and parking lots for the digitization of accounting is substantiated. The methodology and organization of the accounting of costs for the agricultural machinery operation using GPS technology have been improved such as: fuel based on the comparison of the fuel indicators in the tank; lubricants and technological fluids after identifying the time (mileage) of the need for their replacement; salaries of drivers and support staff in proportion to the movement mileage of special equipment while performing production tasks; social insurance funds of employees of agricultural enterprises; depreciation deductions according to the proportional (production method); technical maintenance and current repairs at the end of the planned service life of spare parts, units and aggregates; forecasting the need for repairs to ensure the uninterrupted functioning of agricultural enterprises. Depending on the location of vehicles and special equipment, the order of accounting is proposed: general production costs for moving special equipment to the places of its operation; production costs within the spatial and territorial limits of the main agricultural activity of land cultivation; production costs for the provision of production services by special equipment to third-party customers; transport and procurement costs for transportation of agricultural products to places of their storage or processing. Based on the accumulated information about the costs associated with the agricultural machinery operation, a scheme for operational costing of services provided to third-party customers using the calculation unit - the kilometer of motor vehicles and special equipment movement was developed. Conclusions. The use of the global positioning system in combination with other geo-information technologies forms a significant information resource about the costs on the operation of agricultural machinery for the effective management of agricultural enterprises. Other geo-information technologies, the use of which transforms accounting and management of agricultural activities, are electronic cartography and aerial visual monitoring of agricultural works using drones, which are the subject of further scientific research.